Customers’ Satisfaction in ATM Service - Empirical Evidence from the Leading Bank in Ethiopia - Yohannes Workeaferahu Elifneh; Jagadish Brahma Goulap; Yidnekachew Girma (International Journal of Engineering and Management Research, 2020)
Service offering channels in banking sector has emerged on scene with a variety of forms such as internet banking, mobile banking, and ATM. Mature competition and global finance system have forced to investigate the significance of customer satisfaction. This study was set to assess customers’ satisfaction in ATM service by taking the case of Commercial Bank of Ethiopia (CBE), which is the leading bank in the country, using SERVPERF model. A self-administered questionnaire was used to collect primary data from 385 valid respondents who are customers of CBE, using convenient sampling technique. Data were analysed using SPSS - frequencies and percentages, mean scores, Cronbach alpha, Pearson’s linear correlation and regression analysis. The study was based on the three research objectives: (a) to measure whether ATM service quality corresponds to each dimensions of SERVPERF (b) to analyze the customer satisfaction on ATM service quality, and c) to investigate the level of customer satisfaction. The findings revealed that all the service quality dimensions are significantly and positively associated with the overall customer satisfaction. Besides, Tangibility, Reliability, Responsiveness, Empathy and Assurance are highlighted as significant predictors and key factors in determining the customer satisfaction. But Assurance was found as the most influential predictor of customer satisfaction. The researchers recommend that in order to ensure customer satisfaction improving the performance on all the dimensions of (ATM) service quality is imperative.